2021
DOI: 10.1021/acsnano.1c00896
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Doping of Molybdenum Disulfide for Enhanced Catalytic Polysulfide Conversion in Lithium–Sulfur Batteries

Abstract: Metal sulfides, such as MoS2, are widely investigated in lithium–sulfur (Li–S) batteries to suppress the shuttling of lithium polysulfides (LiPSs) due to their chemical adsorption ability and catalytic activity. However, their relatively low conductivity and activity limit the LiPS conversion kinetics. Herein, the Co-doped MoS2 is proposed to accelerate the catalytic conversion of LiPS as the Co doping can promote the transition from semiconducting 2H phase to metallic 1T phase and introduce the sulfur vacanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(89 citation statements)
references
References 50 publications
2
87
0
Order By: Relevance
“…[ 23,24 ] To overcome current cathode limitations, metal‐based compounds and metal‐organic frameworks have been added to strengthen the chemical interaction with LiPS and reduce the shuttle effect. [ 25–30 ] Among the tested metal compounds, sulfides such as MoS 2 , VS 2 , CoS 2 , Ni 3 S 2 , and Sb 2 S 3 , have demonstrated particularly strong sulfiphilic ability toward LiPS trapping and low lithiation voltages. [ 31–36 ] However, cathodes based on metal sulfides are generally characterized by moderate electrical conductivities, limited sulfur utilization, insufficient cycling stability, and low rate capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] To overcome current cathode limitations, metal‐based compounds and metal‐organic frameworks have been added to strengthen the chemical interaction with LiPS and reduce the shuttle effect. [ 25–30 ] Among the tested metal compounds, sulfides such as MoS 2 , VS 2 , CoS 2 , Ni 3 S 2 , and Sb 2 S 3 , have demonstrated particularly strong sulfiphilic ability toward LiPS trapping and low lithiation voltages. [ 31–36 ] However, cathodes based on metal sulfides are generally characterized by moderate electrical conductivities, limited sulfur utilization, insufficient cycling stability, and low rate capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combining the excellent properties of MoS 2 with other materials can solve the problem of low conductivity . 3D Co-MoS 2 -graphene synthesized by the hydrothermal method could not only alleviate the shuttle effect of the cathode material but could also increase the conduction of electrons and the transfer of Li + (Figure ). The doping of metal Co promoted the transformation of the properties of MoS 2 from the semiconductor to the metal phase.…”
Section: Metal Compounds-based Sulfur Cathode Materials For Li–s Batt...mentioning
confidence: 99%
“…(c) Charge/discharge profiles at different current densities of Co-MoS 2 -G/S. Reproduced from ref . Copyright 2021, American Chemical Society.…”
Section: Metal Compounds-based Sulfur Cathode Materials For Li–s Batt...mentioning
confidence: 99%
“…[116,117] Due to high electrical conductivity, single metal atoms expedite the electrokinetics of polysulfides conversion from long-chain to short-chain polysulfides. [118] It is identified that the metal atoms can lower the decomposition energy barrier of polysulfides due to higher polar-polar interactions and physical/chemical adsorption that speed up the redox kinetics of the battery. [119] In recent years, nanoclusters of various transition metals, for instance, iron, copper, vanadium, and nickel, have been reported to attenuate the dissolution of sodium polysulfides.…”
Section: Chemisorbed S-hostmentioning
confidence: 99%